Batbuyan Batjav's report, Mongolia, September 2021 (Mobilities and Socialities: COVID-19 in the Drylands of Africa and Beyond, 2021)
Includes photographs
Keywords: Herders; Vaccination; Livestock; Food security; Schools; Household Income; Pastoralist; Mongolia; COVID-19 Pandemic